Hematological profile and biochemical markers of COVID-19 non-survivors: A retrospective analysis - Mukesh Bairwa; Rajesh Kumar; Kalpana Beniwal; Deepjyoti Kalita; Yogesh Bahurupi (Elsevier, 2021)
Background: Coronavirus disease is primarily transmitted through the respiratory route and bodily contact. The fatality in COVID-19 cases was alarming in the initial days. This study analyzes hematological and biochemical markers of COVID-19 non-survivors. Material and methods: In this single-center study, records of 249 patients hospitalized with COVID-19 were studied for hematological profile and biochemical markers. Records of patients with laboratory-confirmed COVID-19 disease hospitalized between April 14, 2020, to August 15, 2020, were included in the analysis. Results: Significantly, the disease mortality was associated with increased procalcitonin (P < 0.05), C-reactive protein (P < 0.05), aspartate transaminase (P < 0.05), serum potassium (P < 0.05), neutrophils count (P < 0.05), white blood cell count (P < 0.05), prothrombin time (P < 0.05) and activated prothrombin time (P < 0.05) in patients reported abnormal x-ray findings. Further, patients with abnormal radiological findings significantly showed a reduced level of lymphocyte counts (P < 0.05), oxygen saturation (P < 0.05), and partial oxygen pressure (P < 0.05). Reduced level of aspartate aminotransferase (P < 0.05), alanine aminotransferase (P < 0.05) and lactate dehydrogenase (P < 0.05) reported significant association with mortality among patients with COVID-19. Conclusions: The clinicians may consider the hematological and biochemical parameters in the patients with COVID-19 in future decision-making. These indicators might support clinical decisions to identify high fatality cases and poor diagnosis in the initial admission phase. In COVID-19 patients, we recommend close monitoring on procalcitonin, C-reactive protein, neutrophils count, and white blood cell count as a clinical indicator for potential progression to critical illness.